Antibacterial Properties of Cement Pastes with Addition of Lithium Hydroxide, Cupric Oxide, and Titanium Dioxide - Brescia-Noranmbuena, L (Polish Mineral Engineering Society, 2025)
In order to provide improved functionalities to concrete, new materials are being studied as antibacterial additions. This could result in a reduction in bacteriological hazards bonded to the surfaces of concrete structures, reducing the requirement for cleaning and chloride use. Therefore, this study evaluates the antibacterial action, and the compressive and flexural strength of cement pastes made with different water/cementitious material ratios (0.35, 0.40, and 0.45) and addition percentages of lithium hydroxide (LiOH), cupric oxide (CuO), and titanium dioxide (TiO2) (1%, 3%, 5%, and 10% by weight) separately on Escherichia coli. Antibacterial activity was assessed using inhibition zone measurements, optical density (OD at 600 nm), and colony-forming unit (CFU) counts after exposure to E. coli. Mechanical performance was evaluated through flexural and compressive strength testing at 7 and 28 days. Results show that LiOH decreases the pastes’ strength while producing the highest antibacterial effect due to its high reactivity and pore-inducing behavior; CuO demonstrated the lowest antibacterial effect due to agglomeration issues but increased strength due to its inert nature and filler effect; and TiO2 had an intermediate antibacterial effect with less strength loss than LiOH, although its antibacterial property was not activated by UV require to its photocatalytic mechanism. Also, it was found notable discrepancies between antibacterial assessment methods, highlighting the need for a multi-technique approach to reliably evaluate antimicrobial performance in cement-based materials. Furthermore, the dispersion of microparticles within the paste significantly influenced both antibacterial efficacy and strength development, suggesting that proper mix design and potential use of dispersion aids are critical for industrial applications. As a result, it was concluded that the three compounds could be used as potential additions to concrete to produce an antibacterial effect. Nevertheless, CuO and TiO2 are highly dependent on the dispersion grade, whereas lithium salts are among the best alternatives due to their soluble potential. © 2025, Polish Mineral Engineering Society. All rights reserved.